Mercado de trabalho no estado do Amazonas no período 2019/2020 - Lima, Abner Cristiano Albuquerque de Holanda (Brasil, 2024)
The general objective of this study is to analyze the labor market in the state of Amazonas during the years 2019 and 2020. The specific objectives are: 1) to investigate the effects of the pandemic on workers' income; and 2) verify the characteristics of State workers. For this analysis, data from the Continuous National Household Sample Survey (PNADC) was used. The analysis was carried out using panel data. The results indicate that informal workers were those most affected by the crisis, due to their lower social protection coverage. Furthermore, the less educated population and rural residents also faced disproportionate challenges. The pandemic has exposed social inequality both in the population of Amazonas and in the rest of Brazil, highlighting the most vulnerable groups, which historically face greater difficulties in times of crisis.